RETRACTED: The influence of parents on the physiological and psychological development and behavior of children - Samatova Abiba; Koshmatova Zhyldyz; Zhoroeva Rahat; Nazhimidinova Asylkan; Abdibayitova Apiza (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001